1994
DOI: 10.1161/01.hyp.23.1_suppl.i220
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and renal effects of nifedipine in cyclosporine-associated hypertension.

Abstract: Cyclosporine induces hypertension and widespread vasoconstriction after transplantation in addition to reducing kidney function. We studied hemodynamic, renal, and hormonal effects of monotherapy with nifedipine XL (n=37) in liver transplant recipients within a year after transplant (median, 4.4 months). Systemic hemodynamics were determined with thoracic electrical bioimpedance. Blood pressure before therapy was 172±4/108±2 mm Hg. Sixty-four percent of recipients achieved blood pressures less than 140/90 mm H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Under some circumstances, they appear to improve renal blood flow, although this has not been apparent during long-term therapy in liver transplant recipients. 64 Many have minor or negligible effects on blood levels of calcineurin inhibitors, although nicardipine may have major, unpredictable effects. Doses must be increased cautiously to limit edema, occasional vascular headaches, and symptoms of excess vasodilation in liver transplant recipients in whom cardiac outputs may remain elevated for several months after transplantation.…”
Section: Treatment Principles For Posttransplantation Hypertensionmentioning
confidence: 99%
“…Under some circumstances, they appear to improve renal blood flow, although this has not been apparent during long-term therapy in liver transplant recipients. 64 Many have minor or negligible effects on blood levels of calcineurin inhibitors, although nicardipine may have major, unpredictable effects. Doses must be increased cautiously to limit edema, occasional vascular headaches, and symptoms of excess vasodilation in liver transplant recipients in whom cardiac outputs may remain elevated for several months after transplantation.…”
Section: Treatment Principles For Posttransplantation Hypertensionmentioning
confidence: 99%
“…Calcium channel blockers are considered an ideal first-line agent for the treatment of post-transplantation hypertension [23,24,25] since they can partially counteract the renal vasoconstrictive effects of cyclosporine [26,27,28,29,30,31,32] and have been shown to mediate renal protection through various mechanisms [33].…”
Section: Introductionmentioning
confidence: 99%
“…Calcium antagonists are effective drugs in SH treatment in patients treated with cyclosporine 44,45 and seem to be the antihypertensives of choice 22,25,28,46 . Studies show that the early use of diltiazem (before, during or immediately after transplantation) is associated with a smaller incidence of episodes of rejection, as well as with a better function of the transplanted organ and a smaller incidence of coronary heart disease 22,46 .…”
Section: Treatmentmentioning
confidence: 99%
“…Studies show that the early use of diltiazem (before, during or immediately after transplantation) is associated with a smaller incidence of episodes of rejection, as well as with a better function of the transplanted organ and a smaller incidence of coronary heart disease 22,46 . Calcium antagonists seem to have a protective effect on the kidney 27 , attenuating vasoconstriction produced by cyclosporine 28,38,47,48 , not increasing the glomerular filtration rate 22,45 , the renal plasmatic flow and the filtration fraction 22 . Experimental studies have shown that the same concentration that prevents the entrance of calcium into the renal tubule cells inhibits cyclosporine influx 49 .…”
Section: Treatmentmentioning
confidence: 99%